Influence of Fibre Length on the Behaviour of Polypropylene Fibre Reinforced Cement Concrete - Imtiaz Ahmed Memon; Ashfaque Ahmed Jhatial; Samiullah Sohu; Muhammad Tahir Lakhiar; Zahid Hussain Khaskheli (Salehan Institute of Higher Education, 2018)
Concrete being a mixture of cement, aggregates (fine and coarse) and water, can be used in vast range of applications. It has excellent durability and availability which are its main advantages. Though, concrete is strong in compression it is comparatively weak in tensile loading. Over the years various materials have been used to reinforce concrete to withstand the tensile stresses. Polypropylene fibre is one such fibre which comes in varied sizes, is nowadays being utilized to reinforce concrete. In this study, three PP fibres were used at 0.20%, 0.25% and 0.30% content by weight. The flexural and compressive strengths were determined. Based on the results, it was observed with increase in size of fibre the compressive strength decreased significantly though it was still higher than the controlled sample. The length of PP fibres had significant effect on the compressive strength and flexural strength of concrete. Short PP fibres showed relatively higher compressive strength but lower flexural strength when higher fibre content is used, while long PP fibres achieved lower compressive strength but higher flexural strength than shorter PP fibres. The optimum dosage for both PP fibre sizes was 0.25% at which it achieved increased strength as compared to control sample.